'Intended' and 'unintended' consequences of the privatisation of health and social care systems in Italy in light of the pandemic. (August 2021) - Ciarini, Andrea; Neri, Stefano
This article analyses the long-term effects of privatisation and marketisation on the Italian regional health and social care systems. The research focuses on three Italian regions – Lombardy, Veneto and Lazio – which are representative of three different models of governance in these sectors. We examine the effects of privatisation and marketisation on the health and social care system by discussing how the regional health-care systems have managed the impact of the COVID-19 pandemic. We also shed light on the dramatic consequences of the pandemic crisis on employment levels and working conditions.